Adolescent football players` sleep, wellness and school physical activity over different phases of the year - Brown, G. A.; Veith, S.; Sampson, J. A.; Whalan, M.; Fullagar, H. H. K. (International Journal of Sports Science & Coaching, 2021)
This study aimed to examine differences in sleep and perceived wellness between a group of adolescent academy football(soccer) players from sport high schools (SHS) and regular high schools (RHS) during different phases of the year, with asecondary focus on their school physical activity (s-PA) levels. Data were collected from 51 adolescent football playersfrom one youth Australian academy in two blocks of two weeks (four weeks total). Subjective sleep quantity and quality,wellness and s-PA were assessed through validated daily questionnaires and weekly surveys. MANOVAs and ANOVAsfor repeated measures were conducted to assess sleep and wellness variables across different weeks (school vs. hol-idays, early vs. late season) and between groups (SHS vs. RHS). No differences in sleep or muscle pain were foundbetween players at SHS and RHS (p>0.05). No effect of week (school vs. holidays, early season vs. late season) on sleepquality or wellness was found, nor did hours of s-PA affect sleep duration (all p>0.05). Total sleep time was withinrecommended guidelines and significantly longer sleep times were experienced during the holidays compared to schoolterm (p¼0.002). Overall, adolescent academy football players reported sleep quantities within recommended rangesand had greater sleep volumes during the holidays rather than during school. School type (SHS vs. RHS) and hours ofs-PA had no effect on the players sleep within our cohort. Additionally, it appears perceptual wellness in this populationis unaffected by time of season, or school compared to holidays.